2013
DOI: 10.1021/jp402702u
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Rate Coefficients for the OH + n-, i-, s-, and t-Butanol Reactions Measured Between 220 and 380 K: Non-Arrhenius Behavior and Site-Specific Reactivity

Abstract: Butanol (C4H9OH) is a potential biofuel alternative in fossil fuel gasoline and diesel formulations. The usage of butanol would necessarily lead to direct emissions into the atmosphere; thus, an understanding of its atmospheric processing and environmental impact is desired. Reaction with the OH radical is expected to be the predominant atmospheric removal process for the four aliphatic isomers of butanol. In this work, rate coefficients, k, for the gas-phase reaction of the n-, i-, s-, and t-butanol isomers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(115 citation statements)
references
References 53 publications
15
100
0
Order By: Relevance
“…Rate coefficients were measured under pseudo first‐order conditions in OH, [HCFC‐133a] ≫[OH], by monitoring the temporal profile of OH. The experimental apparatus and methods used in this work are described in more detail elsewhere [ Vaghjiani and Ravishankara , ; McGillen et al, ]. The temperature of the 150 cm 3 Pyrex LIF reactor was controlled to ±0.5 K by circulating a temperature‐regulated fluid through its outer jacket.…”
Section: Methodsmentioning
confidence: 99%
“…Rate coefficients were measured under pseudo first‐order conditions in OH, [HCFC‐133a] ≫[OH], by monitoring the temporal profile of OH. The experimental apparatus and methods used in this work are described in more detail elsewhere [ Vaghjiani and Ravishankara , ; McGillen et al, ]. The temperature of the 150 cm 3 Pyrex LIF reactor was controlled to ±0.5 K by circulating a temperature‐regulated fluid through its outer jacket.…”
Section: Methodsmentioning
confidence: 99%
“…It is this low temperature region for n-butanol where the biggest discrepancies occurred between the simulated and experimental results. The temperature dependence for the overall reaction rate suggested in [29] is based on a fit to both low temperature measurements below 400 K and the high temperature shock tube measurements of [46] , the uncertainty in the overall rate may be larger in the temperature region of interest here. In addition, a previous global sensitivity study of predicted ignition delays for nbutanol at 725 K and 15 bar [28], demonstrated that the sensitivity to the relative rates of abstractions higher uncertainties for the site specific [29].…”
Section: 2mentioning
confidence: 99%
“…McGillen et al [29] to improve the reactivity at lower temperatures. The resulting detailed mechanism consists of 1944 species and 8231 reaction steps.…”
Section: Simulations and Sensitivity Analysismentioning
confidence: 99%
“…(2) rate coefficients for the reactions of Cl, OH, and NO 3 are higher for alcohols than those of the corresponding alkanes due to the activating effect of the OH group, with this effect extending over about four carbon atoms (Nelson et al, 1990); and (3) the attack percentage of a radical to the different sites of the alcohol (α, β, γ , and δ) depends on the oxidant, the structure of saturated alcohol, the type and numbers of substituents, and temperature (Moreno et al, 2012(Moreno et al, , 2014McGillen et al, 2013McGillen et al, , 2016. In order to verify these remarks, the reactivity of the SAs studied in this work were analyzed and discussed by comparing the rate coefficients of the SAs obtained with different oxidants, by comparing the rate coefficients of the SAs and the rate coefficients of their homologous alkanes available in literature, and by comparing the rate coefficients obtained in the reaction of the same oxidant but with different alcohols.…”
Section: Reactionmentioning
confidence: 99%